Ethnomathematics Study: Geometrical Concept in Kudus Market Snacks - Diva Aftina Ardiyanti; Putri Nur Malasari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Most students consider mathematics difficult, because it is abstract. To respond to this, teachers can use ethnomathematics in learning mathematics so that mathematics is easy to understand. One of the ethnomathematics objects that can be used is market snacks. Market snacks are traditional foods that are often sold in crowded places such as markets. This study aims to analyze the geometrical concepts that exist in various forms of market snacks in Kudus. This research uses a type of qualitative research with an ethnographic approach. Data collection used semi-structural interviews with 3 market snack sellers, literature studies, and documentation. The results of the study found that there are geometric concepts in market snacks. Triangular, rectangular, and circular shapes are found, while for spatial shapes, rectangular pyramids, blocks, spheres, triangular prisms, and tubes are found. The research results can be used as an alternative source of learning mathematics, especially in geometry material.